The prevalence of Addison's disease in Coventry, UK. - Willis, A. C. (BMJ Group, 1997)
The prevalence of Addison's disease (chronic adrenal failure) has not been widely investigated and is usually given as 39 in a million. We conducted a prevalence study using a postal survey of general practitioners in Coventry. Three quarters (139/188) replied, representing 79/85 (93%) of the practices. Thirty cases of Addision's disease were found from a total patient list of 323852, of which a third were tuberculous in origin and two-thirds non-tuberculous (12/30 autoimmune, 8/30 unclassified). We conclude that Addison's disease is 2.4 times more common than previously reported. The tuberculous group was older, 65 vs 52 years (p < 0.05), and had had the disease for longer than the non-tuberculous group, 20 vs 12 years (p < 0.05). There was no significant difference in the age at diagnosis.